Avoiding Futility in Simultaneous Liver-kidney Transplantation: Analysis of 331 Consecutive Patients Listed for Dual Organ Replacement. Issue 5 (May 2017) - Lunsford, Keri E.; Bodzin, Adam S.; Markovic, Daniela; Zarrinpar, Ali; Kaldas, Fady M.; Gritsch, Hans Albin; Xia, Victor; Farmer, Douglas G.; Danovitch, Gabriel M.; Hiatt, Jonathan R.; Busuttil, Ronald W.; Agopian, Vatche G.
Abstract : Objective: We sought to evaluate outcomes and predictors of renal allograft futility (RAF—patient death or need for renal replacement therapy at 3 months) after simultaneous liver-kidney transplantation (SLKT). Background: Model for End-Stage Liver Disease (MELD) prioritization of liver recipients with renal dysfunction has significantly increased utilization of SLKT. Data on renal outcomes after SLKT in the highest MELD recipients are scarce, as are accurate predictors of recovery of native kidney function. Without well-established listing guidelines, SLKT potentially wastes renal allografts in both high-acuity liver recipients at risk for early mortality and recipients who may regain native kidney function. Methods: A retrospective single-center multivariate regression analysis was performed for adult patients undergoing SLKT (January 2004 to August 2014) to identify predictors of RAF. Results: Of 331 patients dual-listed for SLKT, 171 (52%) expired awaiting transplant, 145 (44%) underwent SLKT, and 15 (5%) underwent liver transplantation alone. After SLKT, 39% experienced delayed graft function and 20.7% had RAF. Compared with patients without RAF, RAF recipients had greater MELD scores, length of hospitalization, intraoperative base deficit, incidence of female donors, kidney and liver donor risk indices, kidney cold ischemia, and inferior overall survival. Multivariate predictors of RAF included pretransplant dialysis duration, kidney cold ischemia, kidney donor risk index, and recipient hyperlipidemia. Conclusions: With 20% short-term loss of transplanted kidneys after SLKT, our data strongly suggest that renal transplantation should be deferred in liver recipients at high risk for RAF. Consideration for a kidney allocation variance to allow for delayed renal transplantation after liver transplantation may prevent loss of scarce renal allografts.